2017
DOI: 10.3390/ijerph14030241
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Behavioural Characteristics Related to Unintentional Injury in Southeast Chinese Adolescents: Evidence from a School-Based Survey

Abstract: The purpose of this study was to explore the epidemiological features of common unintentional injury-related behaviours and to identify possible factors that lead to these unsafe behaviours among adolescents. A representative sample of 10,806 students was recruited from 77 schools by using the two-stage stratified random sampling method. All participants took a self-administered questionnaires and data were analysed to estimate the prevalence of unintentional injury-related behaviours and to identify the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Injuries are a frequent and sometimes devastating outcome of risk taking but are also inherent in the environment in which adolescents live, study, and play (Sleet et al 2010). The occurrence of unintentional injuries in children is associated with multilevel factors, including but not limited to socioeconomic factors (Gilbride et al 2006;Simpson et al 2005), psychological disorders (Asbridge et al 2014;Chen et al 2005), risk-taking behavior (Feng et al 2017), school environment (Fang et al 2015;ALBashtawy et al 2016) and parenting style (Keyes et al 2014). In China, the ecological model has been introduced to estimate the effects of both individual factors and contextual environments on unintentional injuries among children aged 6-16 in Chongqing, a south-western city (Hu et al 2018).…”
mentioning
confidence: 99%
“…Injuries are a frequent and sometimes devastating outcome of risk taking but are also inherent in the environment in which adolescents live, study, and play (Sleet et al 2010). The occurrence of unintentional injuries in children is associated with multilevel factors, including but not limited to socioeconomic factors (Gilbride et al 2006;Simpson et al 2005), psychological disorders (Asbridge et al 2014;Chen et al 2005), risk-taking behavior (Feng et al 2017), school environment (Fang et al 2015;ALBashtawy et al 2016) and parenting style (Keyes et al 2014). In China, the ecological model has been introduced to estimate the effects of both individual factors and contextual environments on unintentional injuries among children aged 6-16 in Chongqing, a south-western city (Hu et al 2018).…”
mentioning
confidence: 99%
“…a), over 24-28 training sessions in two weeks, the MSP and ETRs of the 32 convalescent stroke patients with hemiplegia showed an overall upward trend during the five upper limb training periods, while during the lower limb training periods, both the MSP and ETRs showed the maximum values in the first period, and then exhibited a slight downward trend. The reasons for these results are as follows: in China, most people have been cycling since childhood, and many have never been able to swim all their lives [53]. In all five assessment training periods (T1-T5), both the MSP and ETRs during the lower limb training were the largest in the first training period of assessment (T1), which indicated that the patients were easy to perform cycling MI at the beginning; in the subsequent training periods of assessment, both the MSP and the ETRs decreased slightly, which may be related to the state of lower limb training of patients at that time.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from Figure 5 , in MSPs and ETRs, there were not many differences among the three patients, and stage 2 of the three patients was all greater than stage 1. These above results were considered to be related to the fact that cycling is relatively easier to imagine than swimming (since most Chinese people have cycling experience, while many do not have swimming experience) [ 48 ]. Therefore, there was no great difference in the performance of the three patients on the task of imagining lower limb cycling, while the imagining upper limb swimming task not only showed greatly different performances among the three patients, but also showed unstable performances in different stages of the same patient [ 47 ].…”
Section: Discussionmentioning
confidence: 99%